SELF-ESTEEM DAN KEPUASAN HIDUP DENGAN FEAR OF MISSING OUT (FoMO) PADA REMAJA - Hasna Farida; Weni Endahing Warni; Lutfi Arya (Jurnal Psikologi Poseidon, 2021)
This study aimed to determine the relationship between self-esteem and fear of missing out (FoMO) and the relationship between life satisfaction and fear of missing out (FoMO) in adolescents. This research used a quantitative approach with survey research methods. The number of subjects as many as 384 youth with an age range of 12-23 years in Surabaya, selected by purposive sampling technique. This study used three scales, namely the self-esteem scale consisting of 12 items, the life satisfaction scale having 14 items and the fear of missing out (FoMO) scale having 15 items. The results showed that there was a relationship between self-esteem and fear of missing out (FoMO) in adolescents with a positive relationship. Other results show that there is a relationship between life satisfaction and fear of missing out (FoMO) in adolescents with a negative relationship. The results of this study can be used as a reference for further research related to fear of missing out (FoMO).